Cogeneration of power and H2 by steam gasification and syngas chemical looping of macroalgae. (1st December 2017) - Zaini, Ilman Nuran; Nurdiawati, Anissa; Aziz, Muhammad
Highlights: A cogeneration system is proposed to convert algae into H2 and power production. The system consists of drying, gasification, chemical looping, and power generation. The system is modeled and evaluated using Aspen Plus software package. The relations between the parameters and the performance of the system are obtained. Abstract: A cogeneration system is proposed in this study to produce H2 and generate power from brown macroalgae with a high moisture content. The processes used in the cogeneration system consisted of drying, steam gasification, syngas chemical looping (SCL), and power generation. Enhanced process integration technology was utilized to maximize heat recovery in the system by minimizing the destruction of exergy. The SCL system used in this study consisted of a fuel reactor, a steam reactor, and an air reactor. Iron oxide was utilized as the circulating oxygen carrier in the SCL system and was reduced and oxidized during its passage through the SCL reactors. The performance of the cogeneration system was evaluated at different target moisture contents during drying, steam-to-biomass ratios during gasification, and operating pressures in the SCL system by means of process simulation using the Aspen Plus software package. The results of the simulation show that the proposed system had a relatively high total efficiency (about 72%), which consisted of H2 production and power generation efficiencies of about 57% and 15%, respectively.